2013
DOI: 10.4271/2013-01-0559
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Pipe Operating Temperature on Exhaust Heat Thermoelectric Generation

Abstract: Increasingly stringent targets on energy efficiency and emissions, as well as growing vehicle electrification are making attractive the electric recovery of the energy normally wasted through the tailpipe of Internal Combustion Engines. Recent developments in thermoelectrics (TE) may soon make them a viable solution for such applications [1]. This team has been exploring the potential of using TE modules in combination with variable conductance heat pipes for transferring the exhaust heat to the generator with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This pressure would vary within controlled values depending on the volume of the system. The authors performed the modelling of aforementioned system, first under fixed pressure and including full experimental validation [11], [12], [14]. Subsequently, the model was applied to realistic driving cycles with fixed pressure/temperature [13] and finally allowing also for realistic pressure variation during the driving cycle [15].…”
Section: Reason For Thermal Controlmentioning
confidence: 99%
“…This pressure would vary within controlled values depending on the volume of the system. The authors performed the modelling of aforementioned system, first under fixed pressure and including full experimental validation [11], [12], [14]. Subsequently, the model was applied to realistic driving cycles with fixed pressure/temperature [13] and finally allowing also for realistic pressure variation during the driving cycle [15].…”
Section: Reason For Thermal Controlmentioning
confidence: 99%
“…Power performance test is conducted under 3 conditions, ie, HP pressure/temperature of, viz., (i) 1 bar/100°C, (ii) 2.7 bar/130°C, and (iii) 6 bar/160°C. Optimum condition is attained at 2.7 bar/130°C where a peak electric power of 25 W is achieved at system efficiency of around 1.2% . Orr et al used HP heat exchanger and 8 commercially available Bi 2 Te 3 modules in a 3.0 l fuel injected V6 engine (vehicle: Holden Commodore).…”
Section: Application Of Teg In Ic Engine‐driven Vehiclesmentioning
confidence: 99%
“…B, HP‐exhaust thermoelectric generator assembly. C, Top view and lower view of condenser blocks (adapted from Brito et al) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Application Of Teg In Ic Engine‐driven Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Brito et al 22 presented an experimental and theoretical study on the influence of the heat pipe temperature in the electric output of a TEG connected to a small diesel engine. Their research demonstrated a possible method for estimating an optimal variable conductance the heat pipe's temperature to maximize the power output.…”
Section: Introductionmentioning
confidence: 99%